2009
DOI: 10.1167/9.13.14
|View full text |Cite
|
Sign up to set email alerts
|

Catching fly balls in virtual reality: A critical test of the outfielder problem

Abstract: How does a baseball outfielder know where to run to catch a fly ball? The “outfielder problem” remains unresolved, and its solution would provide a window into the visual control of action. It may seem obvious that human action is based on an internal model of the physical world, such that the fielder predicts the landing point based on a mental model of the ball’s trajectory (TP). But two alternative theories, Optical Acceleration Cancellation (OAC) and Linear Optical Trajectory (LOT), propose that fielders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 30 publications
5
123
0
1
Order By: Relevance
“…Two other studies that experimentally manipulated object trajectories in midflight were done by Fink, Foo, andWarren (2009) andMcLeod et al (2008). McLeod et al (2008) showed that GOAC was able to account for the optical trajectories observed for soccer ball interception ("headers").…”
Section: Research Using Midflight Disturbances To Object Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies that experimentally manipulated object trajectories in midflight were done by Fink, Foo, andWarren (2009) andMcLeod et al (2008). McLeod et al (2008) showed that GOAC was able to account for the optical trajectories observed for soccer ball interception ("headers").…”
Section: Research Using Midflight Disturbances To Object Trajectoriesmentioning
confidence: 99%
“…1 Fink et al (2009) performed a virtual reality test of people chasing baseballs where the direction of the ball was changed in midflight. They concluded that the nonsegmented version of LOT could not explain the perturbed trajectories, while OAC (and thus, GOAC) could (Fink et al, 2009).…”
Section: Research Using Midflight Disturbances To Object Trajectoriesmentioning
confidence: 99%
“…There is a great deal of interest in training sporting skills using virtual environments (VEs), for example handball [1], [2], tennis [3], [4], [5], golf [6], [7], [8], baseball [9], [10], [11], cycling [12] and swimming [13]; and discussion concerning the validity of VEs as a training tool for a wide array of different activities [14], [15], [16]. The discussions focus on the possibility of detrimentally affecting the user by teaching a new skill incorrectly or spoiling a skill the user already possesses by providing a training platform that lacks vital cues or provides superficial cues that are not present in the real world.…”
Section: Introductionmentioning
confidence: 99%
“…Action fidelity is a particularly important methodological issue, given the growing use of virtual environments within research and training contexts (e.g. Fink, Foo, & Warren, 2009;Chan, Leung, Tang, & Komura, 2011;Vignais et al, 2009) Data on adaptations to postural regulation behaviors and the kinematics of the catching arm in the three conditions suggested that the catching action was 'nested' on the task of postural regulation (see Riccio & Stoffregen, 1988). This coordination strategy reduced the number of system degrees of freedom that the CNS needed to regulate in an "umbrella" control strategy, with posture being dependent on the task being performed.…”
Section: Cop and Commentioning
confidence: 99%